ONTOLOGI HIKAYAT PRANG SABI - Hardiansyah Hardiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Hikayat Prang Sabi is a work produced by an Acehnese. It is comprised of calls for fighting in path of Allah (Jihad). The hikayat (tale) is based on Qur-an and Hadist. The discourse in this writing is metaphysical aspect that is constituted in. Its cosmology metaphysical aspect is another power that can influence life. The essence is to defend religion, Islam. Ecstatic metaphysical value is also revealed, that is the perfect beauty in the meeting with the highest reality (ilahi) which becomes the idea of those fighting in path of Allah.